(untitled) (Marketing Journal, 2026)
Abstract This article highlights the existing mechanisms for recovering problem loans in pre-trial and judicial proceedings, as well as opportunities for their improvement. During the study, the main problems encountered in the recovery of problem loans were analyzed, and existing legal norms, banking practice, and execution processes were studied. Also, relevant approaches and proposals and recommendations have been formed to improve the efficiency of working with debtors at the pre-trial stage, and to simplify and accelerate the collection mechanisms in the judicial process. Keywords: problematic loan, loan in litigation, overdue debt, diversification, risk.